OPTIMIZING TOTAL IDLE TIME IN A MIXED-MODEL ASSEMBLY LINE THROUGH WORKLOAD ADJUSTMENT - Dr. Anoop Kumar Elia; Dr. Sangamesh Sirsgi; Abhishek Yedve (International Educational Journal of Science and Engineering, 2026)
The fundamental of ALBP is to minimize and assign the number of workstations; minimize balance delay; and line balancing loss, idle time minimizing, minimizing CT. The purpose of the ALBP is to distribute the activities equally to the available workstations, this in turn increases the utilization of human resourced and the available facilities. The MMuALB is used to optimize for the best performance to reduce the losses. Four models with different quantities of production are treated for assembly line optimization. The TNOS required for optimise allocation are considered. The algorithm was used to demonstrate 19 task problem which minimizes balancing and system loss. The quantities of models to be producedare10eachforallthe four models. The algorithm developed is based on branch and bound technique. Buxey 29 task based problem is considered for solution for least idle time of the work stations.